2010
DOI: 10.1103/physreve.81.056204
|View full text |Cite
|
Sign up to set email alerts
|

Design of easily synchronizable oscillator networks using the Monte Carlo optimization method

Abstract: Starting with an initial random network of oscillators with a heterogeneous frequency distribution, its autonomous synchronization ability can be largely improved by appropriately rewiring the links between the elements. Ensembles of synchronization-optimized networks with different connectivities are generated and their statistical properties are studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…To avoid the effect of the biased sampling, we deterministically select the natural frequencies of the oscillators, similarly to [11], as the N -tuple satisfying the constraints:…”
Section: Problem Statementmentioning
confidence: 99%
“…To avoid the effect of the biased sampling, we deterministically select the natural frequencies of the oscillators, similarly to [11], as the N -tuple satisfying the constraints:…”
Section: Problem Statementmentioning
confidence: 99%
“…Previously, similar problems were treated by using a stochastic Monte Carlo algorithm with replica exchange [15] (the design of networks of identical phase oscillators with maximal synchronization in the presence of noise has also been considered [16]). Now we want to show how to construct an autonomous dynamical system that would include as its subsystem a network of phase oscillators and independently evolve to a state with a desired degree of synchronization.…”
Section: R = F(x)mentioning
confidence: 99%
“…However, rational design rapidly becomes difficult when the size of a system is increased and a complex combinatorial optimization problem is approached. Combinatorial optimization methods, such as stochastic Metropolis algorithms and simulated annealing, have been used in systems engineering problems [7][8][9][10][11][12][13][14][15][16]. Thus, analogs of biological signal transduction networks [7][8][9][10] and model oscillatory genetic networks with prescribed output patterns or oscillation periods [11,12] could be constructed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By using the technique of pinning only a limited subset of the whole network, [17] showed that the complex network with coupled identical oscillators could be driven onto some desired common reference trajectory. Nowadays, more and more attentions are being paid to the optimization problems of pinning schemes [18][19][20][21]. For instance, the crucial problem that how to select an optimal combination between the number of pinned nodes and the feedback control gain is studied in [19].…”
Section: Introductionmentioning
confidence: 99%